Seed‐applied Fungicide and Inoculant Interactions for Late‐planted Soybean in the Mid‐southern United States. Issue 1 (5th February 2016) - Golden, Bobby R.; Allen, Tom W.; Orlowski, John M.
Abstract : Soybean [ Glycine max (L.) Merr.] production has recently replaced cotton ( Gossypium hirsutum L.) production on a large number of acres in the mid‐southern United States. Seed‐applied inoculants and fungicides are common management inputs to help soybean producers deal with limited Bradyrhizobium japonicum populations and soilborne diseases associated with early planting (April) that is standard for soybean production in Mississippi. However, it is unclear if seed‐applied inoculants and fungicides are necessary for late‐planted (May or June) soybean in fields with a history of nonsoybean or following flooded conditions. Studies were conducted at four late‐planted locations during the 2011 and 2012 growing seasons in Mississippi, planted between May (2011; n = 1) and mid‐ to late June (2011, 2012; n = 3). Three common seed‐applied fungicide products (ApronMaxx RTA, ApronMaxx RFC, and Trilex 6000) and two seed‐applied inoculant products (Optimize and Vault‐HP) were applied alone and in combination. Within‐season plot evaluations were conducted to determine the effects on soybean stand and yield. Postharvest evaluations considered important soybean seed quality characteristics (e.g., damaged seed, mold). Seed‐applied inoculant products did not affect soybean stands, but ApronMaxx RFC increased soybean stands by >8% compared with nontreated soybean and soybean treated with the other fungicide products. An inoculant × fungicide interaction was observed for soybean yield. ApronMaxx RFC without an inoculant and Trilex 6000 with Optimize increased yield by 7% over nontreated soybean. Performance of seed‐applied fungicides appeared to vary depending on the type of inoculant used.